Daya Hambat Asap Cair Kayu Karet terhadap Bakteri Pengkontaminan Lateks dan Ribbed Smoke Sheet - Karseno Karseno; Purnama Darmadji; Kapti Rahayu (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2001)
The objective of this research was to study the antibacterial activities of rubber wood liquid smoke. The activities were tested to latex and sheet contaminating bacteria. This research was conducted in several steps i.e. isolation and identification of bacteria, test of the antibacterial activities of liquid smoke and analysis of the antibacterial component. Agar diffusion method was used to evaluate the antibacterial activities. The result indicated that liquid smoke could inhibit the growth of latex and ribbed smoke sheet contaminating bacteria. The liquid smoke still showed bateri activities after 50 times and 20 times dilution respectively. Phenols (phenol, cresol, guaiacol) and organic acids (acetic acid and propionic acid) were antibacterial components in liquid smoke of rubber wood.